Coplanar waveguide to coplanar strips-fed active leaky-wave antenna - Hu, CC; Jou, CF; Wang, CJ; Lee, SH; Wu, JJ (My University, 1998)
A new active coplanar waveguide (CPW) to coplanar ships (CPS)-fed microstrip leaky-wave antenna is developed, which is integrated with a Gunn diode as an active source. The CPW-CPS balun is used to excite the first higher order mode of the microstrip leaky-wave antenna. The active leaky-wave antenna has a maximum EIRP of 20.4 dBm at 9.759 GHz. The Gunn oscillator frequency is controlled by tuning the Gunn de bias, and the beam scanning is demonstrated. The measured scanning angle agrees with the prediction; it is close to 12 degrees as the oscillator frequency is tuned from 9.84 to 9.61 GHz. The coplanar structure allows easy integration of many solid-state devices. It is suitable for monolithic power combining ann millimeter-wave applications. (C) 1998 John Wiley & Sons, Inc.
Keywords: leaky-wave antenna; CPW; CPS; scanning; Gunn oscillator